Severe Air Pollution and School Absences: Longitudinal Data on Expatriates in North China - Haoming Liu; Alberto Salvo (Institute of Labor Economics (IZA), 2017)
Little is known about how children of high-income expatriate families, often from rich nations, adapt to temporary residence in a severely polluted city of the developing world. We use a six-year panel of 6,500 students at three international schools in a major city in north China to estimate how fluctuation in ambient PM2.5 over the preceding fortnight impacts daily absences. Our preferred estimates are based on the exclusion restriction that absences respond to atmospheric ventilation such as thermal inversions only through ventilation's effect on particle levels. A large and rare 100 to 200 μg/m3 shift in average PM2.5 in the prior week raises the incidence of absences by 1 percentage point, about one-quarter of the sample mean. We find stronger responses for US/Canada nationals than among Chinese nationals, and among students who generally miss school the most. Overall responses are mod-est compared to the effect on absences from more moderate in-sample variation in pollution estimated for the US using aggregate data. Using school absence patterns as a window into short-run health and behavior, our study suggests that high-income families find ways to adapt, likely by moving life indoors, even if temporary residence in north China comes at the expense of long-term health.
Keywords: I18; J24; Q51; 330; environmental valuation; environmental damage; environmental health; atmospheric ventilation; thermal inversions; heterogeneous effects; longitudinal study; acute exposure; PM2.5; particulate matter; air pollution; school absences; avoidance behavior; distributed lags; instrumental variables